Pengaruh Risiko Kredit dan Tingkat Likuiditas Terhadap Profitabilitas Perbankan Yang Terdaftar di BEI Periode Tahun 2018-2022 - Novil Gabriel Sagara-gara; Bagun Putra Prasetya (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to analyze the effect of liquidity and credit risk on the profitability of banks listed on the Indonesia Stock Exchange (IDX) during the period 2018–2022. Profitability is measured by Return on Assets (ROA), liquidity is proxied by the Loan to Deposit Ratio (LDR), while credit risk is measured using the Non-Performing Loan (NPL) ratio. The research employs a quantitative approach with multiple linear regression analysis to test the partial and simultaneous influence of the independent variables on profitability. Data were obtained from the annual financial reports of banks published on the IDX, covering a five-year observation period. The results of the analysis show that credit risk, as measured by NPL, has a significant negative effect on bank profitability. This finding reflects that the higher the NPL ratio, the lower the bank’s ability to generate returns on assets, emphasizing the importance of effective credit quality management. In contrast, the liquidity level measured by LDR demonstrates a positive but statistically insignificant effect on ROA. This suggests that although liquidity plays a role in supporting banking operations, its direct impact on profitability is relatively weak when considered independently. However, when examined simultaneously, both credit risk and liquidity significantly affect bank profitability. These findings imply that effective credit risk management is a crucial determinant of financial performance in the banking sector. High levels of non-performing loans can erode bank profits, while optimal liquidity management supports operational efficiency, even if its impact is not strongly significant in isolation. From a managerial perspective, banks need to strengthen monitoring of loan quality, implement more prudent credit policies, and adopt sustainable liquidity strategies to enhance profitability. For regulators, the results highlight the importance of supervising asset quality and ensuring adequate liquidity management in the banking system. This study contributes to the literature on banking performance by providing empirical evidence on the interaction between credit risk, liquidity, and profitability in the Indonesian banking sector.